A bee pupa-infilled honeycomb structure-inspired Li2MnSiO4 cathode for high volumetric energy density secondary batteries. Issue 25 (19th February 2019) - Liu, Jinyun; Lin, Xirong; Zhang, Huigang; Shen, Zihan; Lu, Qianqian; Niu, Junjie; Li, Jinjin; Braun, Paul V.
Abstract : A novel biomimetic mesostructured cathode is reported, which provides a new method for improving active material loading of porous electrodes. Abstract : Emerging power batteries with both high volumetric energy density and fast charge/discharge kinetics are required for electric vehicles. The rapid ion/electron transport of mesostructured electrodes enables a high electrochemical activity in secondary batteries. However, the typical low fraction of active materials leads to a low volumetric energy density. Herein, we report a novel biomimetic "bee pupa infilled honeycomb"-structured 3D mesoporous cathode. We found previously the maximum active material filing fraction of an opal template before pinch-off was about 25%, whereas it could be increased to ∼90% with the bee pupa-infilled honeycomb-like architecture. Importantly, even with a high infilling fraction, fast Li + /e − transport kinetics and robust mechanical property were achievable. As the demonstration, a bee pupa infilled honeycomb-shaped Li2 MnSiO4 /C cathode was constructed, which delivered a high volumetric energy density of 2443 W h L −1 . The presented biomimetic bee pupa infilled honeycomb configuration is applicable for a broad set of both cathodes and anodes in high energy density batteries.